2004
DOI: 10.1517/phgs.5.1.67.25683
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Polymorphism of Drug Transporters: Functional Analysis Approaches

Abstract: Evidence is accumulating to strongly suggest that drug transporters are one of the determining factors governing the pharmacokinetic profile of drugs. To date, a variety of drug transporters have been cloned and classified as solute carriers and ATP-binding cassette transporters. Such drug transporters are expressed in various tissues such as the intestine, brain, liver, and kidney, and play critical roles in the absorption, distribution and excretion of drugs. However, at the present time, information is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 157 publications
0
41
0
2
Order By: Relevance
“…To clarify the interindividual variation in the pharmacokinetics of drugs, single-nucleotide polymorphisms (SNPs) in the coding region (cSNP) of drug transporters have been investigated (Ishikawa et al, 2004). Erdman et al (2006) examined the allele frequency of several cSNPs in the OAT3 gene and transport characteristics and found that allele frequencies of cSNPs, which resulted in a completed loss of function, were very low (Xu et al, 2005;Erdman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the interindividual variation in the pharmacokinetics of drugs, single-nucleotide polymorphisms (SNPs) in the coding region (cSNP) of drug transporters have been investigated (Ishikawa et al, 2004). Erdman et al (2006) examined the allele frequency of several cSNPs in the OAT3 gene and transport characteristics and found that allele frequencies of cSNPs, which resulted in a completed loss of function, were very low (Xu et al, 2005;Erdman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition to drug-metabolizing enzymes, the clinical significance of genetic variation of drug transporters has been demonstrated. 13 For example, polymorphisms of SLCO1B1, which encodes the organic anion transporting polypeptide 1B1 to mediate the hepatic uptake of pravastatin, contribute to the interindividual variability in the disposition of pravastatin. 14 Recent studies of OCT have demonstrated that polymorphisms of the OCT1 gene in Caucasians and the renal OCT2 gene in Koreans are responsible for the interindividual differences in the therapeutic efficacy and pharmacokinetics of metformin, an anti-diabetic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Function analysis of the gene products of some CYPs and transporters, along with their variants, were also conducted. 2 Some of these findings have already been published, and others will be published shortly. Cell lines were also established from the samples and deposited in the Health Science Research Resources Bank.…”
Section: Establishment Of Pharmacoge-nomics Platforms By Industrymentioning
confidence: 95%